2020
DOI: 10.1016/j.jad.2019.09.043
|View full text |Cite
|
Sign up to set email alerts
|

What do patients learn about psychotropic medications on the web? A natural language processing study

Abstract: Background: Low rates of medication adherence remain a major challenge across psychiatry. In part, this likely reflects patient concerns about safety and adverse effects, accurate or otherwise. We therefore sought to characterize online information about common psychiatric medications in terms of positive and negative sentiment. Methods:We applied a natural language processing tool to score the sentiment expressed in web search results for 51 psychotropic medications across 3 drug classes (antidepressants, ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 23 publications
0
13
0
Order By: Relevance
“…A total of 3 studies were on violence and cyber harassment [ 40 , 80 , 94 ]. Treatment issues such as adherence or misuse are also depicted (6 cases) [ 56 , 72 , 74 , 81 , 101 , 103 ]. Only 1 study on mechanical restraints [ 90 ] and 1 on cognitive troubles [ 97 ] were found.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 3 studies were on violence and cyber harassment [ 40 , 80 , 94 ]. Treatment issues such as adherence or misuse are also depicted (6 cases) [ 56 , 72 , 74 , 81 , 101 , 103 ]. Only 1 study on mechanical restraints [ 90 ] and 1 on cognitive troubles [ 97 ] were found.…”
Section: Resultsmentioning
confidence: 99%
“…It has been used by researchers for the sentiment analysis of the social media texts in a variety of disciplines, e.g. online health information (experiences and opinions of the patients regarding the treatments received), (Hart et al, 2020), movie reviews posted online where VADER outperformed other sentiment analyzers such as Textblob and NLTK (Kumaresh et al, 2019), product reviews posted by the consumers on the Amazon (Bag et al, 2019), etc. This study uses VADER to compute the daily average positive and negative scores, to represent the daily optimistic and pessimistic public sentiments on the Twitter for each sector, as following:…”
Section: Sentiment Analysismentioning
confidence: 99%
“…A total of 3 studies were on violence and cyber harassment [40,80,94]. Treatment issues such as adherence or misuse are also depicted (6 cases) [56,72,74,81,101,103]. Only 1 study on mechanical restraints [90] and 1 on cognitive troubles [97] The authors of these studies have selected specific hashtags such as #stress or #depression and have screened a multitude of public messages using a streaming platform.…”
Section: Study Selectionmentioning
confidence: 99%